STUDI ISLAM DENGAN PENDEKATAN ORIENTALISME - Priliansyah Ma’ruf Nur (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2019)
Islam which was spread by the Prophet Muhammad SAW in the 7thcentury in Arab lands has spread now throughout the world. This religion isknown by Western scholars (Orientalists) as Eastern religions (Orient). In itsprogress, Islam became a new force in the world political arena which wasfeared by people in the West. Starting from the expansion carried out by theUmayyad Dynasty, the Abbasid Dynasty, and culminating in the tragedy ofthe Crusades. These sentiments became the negative views of Westerners whodid not like the presence of Islam. They tend to judge Islam as a religion ofwar, irrational, anti-world, anti-progress, sexual religion, wasteful religion, andso on. However, in its history the Orientalists studied Islam through severalperiods, namely the Pre-Crusade period, the Crusades, the Enlightenment untilthe 19th century, and in the 20th century who had begun objectively in studyingIslam as a religion of salvation, a religion that was peace, and pro progress.